A study on the adequancy of the aboriginal peoples act 1954 in protecting indigenous land in Malaysia / Liah anak Asul ...[et al.] - Asul, Liah; Gabil, Maseirfan Syamshulbahri; Hamzah, Mohd Firdaus; Kamarullah, Mohd Ridhwanuddin; Mohd Ishak, Nur Zalikha (2010)
This research is a legal study on the adequacy of the Aboriginal People's Act 1954 in protecting the indigenous land in Malaysia. The research which has been conducted is somehow in comparison to the Australia as Australian system towards the indigenous peoples land is better than the system which we have back here in Malaysia. This study sets out to discover the position of indigenous peoples land in Malaysia and also in Australia. This study also seeks to discover whether the Australian system of indigenous peoples land may be adapted to the Malaysian current situation. In "Australia, their system is known to be as a system which gives better protection to the indigenous peoples where their system recognizes the position of indigenous peoples land. Due to this fact, we found that the Australian system may be suitable to be adapted into Malaysian system that we are using right now in order to give more recognition to the indigenous peoples land. However, this adaption from the Australian system should be amended so that it fits to the uniqueness of Malaysian society.